Improvement of MIMO System using STTC with Artificial Neural Network - Raad H. Thahir (Diyala Journal of Engineering Sciences, 2017)
The wide demand for high data rate rapid development in mobile and internet communication system limitation of the radio spectrum and the communication capacity needs cannot be met without a significant increase in communication spectral efficiency make it important to increase the capacity and decrease the Bit Error Rate (BER) of communication channel. In this paper, analysis of the capacity for four types of communication systems are performed, it was found that the MIMO communication system capacity is the best, Space Time Trellis Code (STTC) technique is used to improve the performance of MIMO system by decreasing the BER as well as possible, finally artificial neural network was used at the receiver of with (STTC) to get more suitable results by decreasing the BER of the proposed system.